Aeroacoustic Analysis Of A Transitioning Vectored-Thrust/Tilt-Rotor UAM Vehicle Using The LB/VLES Method - Di Verniere, F.; Sticchi, E.; Casalino, D.; Ragni, D.; Zamponi, R. (My University, 2025)
A high-fidelity aeroacoustic simulation of a full-scale electric vertical take-off and landing vehicle was performed to investigate the transition maneuver from vertical ascent to forward flight. The study employed a Lattice Boltzmann method, enabling the resolution of complex unsteady aerodynamic phenomena while maintaining manageable computational costs. The analysis revealed that aerodynamic interactions between rotors, nacelles, and the wing significantly affect the distribution of aerodynamic forces, with rotor-wing interference playing a key role in lift and drag behavior. Acoustic emissions were evaluated in the far field using a permeable formulation of the Ffowcs Williams-Hawkings analogy on a spherical array representative of an urban air mobility operational context. The results highlighted clear directional patterns and a harmonic-dominated frequency spectrum. The findings offer critical insights into the coupled aerodynamic and acoustic behavior of eVTOLs during transition and provide a high-fidelity reference to support the validation of lower-order design tools.